Breastfeeding and the Occurrence of Diarrheal Dehydration in Toddler - Windha Widyastuti; Yuni Sandra Pratiwi; Nurul Aktifah; Isyti’aroh Isyti’aroh (Proceedings Series on Health & Medical Sciences, 2021)
Dehydration which is often caused by diarrhea is the leading cause of death in children under five. The severity of diarrhea can be prevented by breastfeeding as the mother's immunity transfers to her baby. This study aimed to describe the relationship between the history of early initiation of breastfeeding, exclusive breastfeeding, and their sustainability with the occurrence of diarrheal dehydration among toddlers. This descriptive correlation study was conducted among a total sampling of toddlers undergoing inpatient due to diarrhea at the Regional Hospital of Pekalongan Regency by 61 respondents. Data were collected from August to September, 2020, using demographic data, the history of early initiation of breastfeeding, the history of exsclusive breastfeeding, the sustainability of that variables, and the occurrence of diarrheal dehydration. Chi-Square was used to find out the relationship between the variables. This study showed that the relationship between either early initiation of breastfeeding or exclusive breastfeeding and the occurrence of diarrheal dehydration was not significant (p= 0,092, and p= 0,064, respectively). Interestingly, there was a relationship between the sustainability of early initiation of breastfeeding and exclusive breastfeeding with diarrheal dehydration among hospitalized toddlers due to diarrhea (p= 0,029). Health care providers especially nursing in the labor room, should give more information about the importance of initiation of breastfeeding and the sustainability of it with exclusive breastfeeding among mothers after giving birth for preventing the occurrence of dehydration due to diarrhea among children in future.